Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae) - Nguyen, Anh D. (Zootaxa, 2016)
A survey in Cuc Phuong National Park has revealed the first record of a xystodesmid millipede in Vietnam and also the southernmost locality for the family in Asia. A new genus and species, Parariukiaria cucfuongensis gen. nov, sp. nov. is proposed and described. In addition, three former Riukiaria species from Sichuan Province (China) are reallocated to the new genus, Parariukiaria belousovi (Golovatch, 2014) comb. nov., P. korolevi (Golovatch, 2014) comb. nov., P. kabaki (Golovatch, 2014) comb. nov.. A key to species of the new genus is also provided.